Arthroscopic Distal Clavicle and Medial Border of Acromion Resection for Symptomatic Acromioclavicular Joint Osteoarthritis - Adinun Apivatgaroon, M.D.; Prakasit Sanguanjit, M.D. (Arthroscopy Techniques, 2017)
Acromioclavicular joint osteoarthritis can lead to persistent shoulder pain. Distal clavicle excision is the most common operative procedure in patients with failed, conservative symptomatic acromioclavicular joint osteoarthritis treatment, with some reports of complications. This report describes an alternative procedure that can be used to excise the distal clavicle together with the medial border of the acromion. This technique is a simple procedure because the standard distal clavicle excision can preserve the acromioclavicular ligament, as well as the joint capsule, and achieve an adequate resection length.